Development of epoxidized palm oil based coating material from used cooking oil and its adhesion performance: article - Abu Kassim, Muhammad Nadzmi; Yaakob, Najmiddin (2019)
Used cooking oil thrown away as waste could possibly causing pollution. By utilizing the used cooking oil which is additional component in formulating new epoxy coating, this could contribute in increasing sustainability of palm oil industry. In the same time, dependency on epoxy resin which has been used as main raw material in epoxy coating can be minimized because of it harmful effects towards human health. Used cooking oil experienced epoxidation process to add oxirane ring into the structure of fatty acid. Oxirane ring provide reactive site for crosslinking process in coating formulation. Formulated coating was then tested for their adhesion performance to determine the best coating’s formulation which gives the best adhesion on the substrate. Result from X-Cut tape test showed that minimal adhesion performances were obtained from every coating formulation. This is in conjunction with spectrum analysis of used cooking oil before and after epoxidation where it showed that there is non-existence of oxirane ring in the epoxidized cooking oil. Adhesion performance results from Cross-Cut tape test have no distinctive trend that can be supported by fourier transform infrared spectroscopy (FTIR) analysis.